High Cytotoxicity and Apoptotic Effects of Natural Bioactive Benzofuran Derivative on the MCF-7 Breast Cancer Cell Line - Soleimani, Afsane; Asadi, Jahanbakhsh; Rostami-Charati, Faramarz; Gharaei, Roghaye (Combinatorial Chemistry & High Throughput Screening, 2015)
This study was focused on evaluation of the cytotoxicity and apoptotic affects of benzofuran derivative on MCF-7 breast cancer cell line. This effective compound was isolated from the root of Petasites hybridus plant. For experiments, the MCF-7 cells were treated with several concentrations (0-500μM) of 1-(6-hydroxy-2- isopropenyl-1-benzofuran-5-yl)-1-ethanone 1 at different times. In this study, test of neutral red was also employed for cytotoxicity assay and quantity of P53, P21. Bax genes expression was analyzed using Real-Time PCR and ELISA techniques. Results show that compound 1 has cytotoxicity and apoptotic effects on Human breast cancer (Michigan Cancer Foundation-7) MCF-7 cells.
Keywords: benzofuran derivative